Different Functions of Recombinantly Expressed Domains of Tenascin-C in Glial Scar Formation - Bijelić, Dunja; Adžić, Marija; Perić, Mina; Jakovčevski, Igor; Förster, Eckart; Schachner, Melitta; Andjus, Pavle R. (Frontiers in Immunology, 2021)
Extracellular matrix glycoprotein tenascin-C (TnC) is highly expressed in vertebrates during embryonic development and thereafter transiently in tissue niches undergoing extensive remodelling during regeneration after injury. TnC’s different functions can be attributed to its multimodular structure represented by distinct domains and alternatively spliced isoforms. Upon central nervous system injury, TnC expression is secreted into the extracellular matrix mainly by astrocytes and upregulated under conditions of injury and learning and memory. The goal of the present study was to elucidate the role of different TnC domains in events that take place after spinal cord injury (SCI). Cortical astrocyte cultures prepared from TnC-deficient (TnC-/-) and wild-type (TnC+/+) littermate mice were scratched and treated with different recombinantly generated TnC fragments. Gap closure, cell proliferation and expression of GFAP and cytokines were determined in these cultures. Gap closure in vitro was found to be delayed by TnC fragments, an effect mainly mediated by decreasing proliferation of astrocytes. The most potent effects were observed with fragments FnD, FnA and their combination TnC-/- astrocyte cultures exhibited higher GFAP protein and mRNA expression levels, regardless of the type of fragment used for treatment.. Application of TnC fragments induced also pro-inflammatory cytokine production by these astrocytes. In vivo, 7 days after SCI, intradural injection of fragments FnD or Fn (D+A) into the cauda equina of spinal cord-injured mice showed a difference in recovery from SCI between the two genotypes, the fragments’ effects being more pronounced in TnC-/- mice than in TnC+/+ mice. FnD treatment of injured TnC-/- mice increased the density of activated microglia/macrophages in the injury region, while overall cell proliferation in the injury site was not affected by the injury. We suggest that altogether these results may explain how activation of astrocytes is reduced and their localization is restricted to the border of the injury site to allow microglia/macrophages to form a lesion core during the first stages of glial scar formation, as mediated by TnC and, in particular, the alternatively spliced FnD domain.